1999
DOI: 10.1021/jm980471k
|View full text |Cite
|
Sign up to set email alerts
|

Ajoene Is an Inhibitor and Subversive Substrate of Human Glutathione Reductase and Trypanosoma cruzi Trypanothione Reductase:  Crystallographic, Kinetic, and Spectroscopic Studies

Abstract: Ajoene ((E,Z)-4,5,9-trithiadodeca-1,6,11-triene 9-oxide), a garlic-derived natural compound, is a covalent inhibitor as well as a substrate of human glutathione reductase (GR) and Trypanosoma cruzi trypanothione reductase (TR). The 2.1-A resolution crystal structure of GR inhibited by (E)-ajoene revealed a mixed disulfide between the active site Cys58 and the CH2=CH-CH2-SO-CH2-CH=CH-S moiety of ajoene. The modified enzyme has a markedly increased oxidase activity when compared to free GR. GR reduces (Z)-ajoene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 47 publications
6
86
0
2
Order By: Relevance
“…The enzyme has been identified as one of the target molecules of the widely applied antitumor drug bis-chloroethylnitrosourea (Frischer and Ahmad, 1977), and a target of ajoene, a compound present in the garlic extract. Its inactivation may result in a 400-fold increased activity of NADPH oxidase (NOX), generating superoxide (Gallwitz et al, 1999). As it is the case with many antioxidant enzymes, Nrf2 is a key regulator of GR expression (Harvey et al, 2009).…”
Section: Recycling Of Consumed Glutathionementioning
confidence: 99%
“…The enzyme has been identified as one of the target molecules of the widely applied antitumor drug bis-chloroethylnitrosourea (Frischer and Ahmad, 1977), and a target of ajoene, a compound present in the garlic extract. Its inactivation may result in a 400-fold increased activity of NADPH oxidase (NOX), generating superoxide (Gallwitz et al, 1999). As it is the case with many antioxidant enzymes, Nrf2 is a key regulator of GR expression (Harvey et al, 2009).…”
Section: Recycling Of Consumed Glutathionementioning
confidence: 99%
“…82 They showed that ajoene 118, another garlic-derived natural product, affects the antioxidant thiol metabolism of T. cruzi, leading to increased oxidative stress by inhibition of the trypanothione reductase. 82 Manumycin A 119, an antibiotic produced by Streptomyces microorganisms, is an inhibitor of Ras farnesyltransferase, which is of interest for antitumor therapy. Compound 119 is potently active in vitro against the growth of both bloodstream and procyclic forms of T. b. brucei (IC 50 = 1.5 and 0.4 µM respectively).…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Using either rational or empiric approaches, different classes of compounds, including peptides and peptoid, substituted polyamines, quinacrine and acridine analogues, 2-aminodiphenylsulfides, phenothiazine derivatives, substituted piperazines and nitrofuran derivatives, were studied for their inhibitory potential (see reviews by Werbovetz 2000, Augustyns et al 2001, Schmidt & KrauthSiegel 2002. Investigation of natural products, although not so extensive, disclosed interesting inhibitors such as ajoene from garlic (Gallwitz et al 1999), bisbenzylisoquinoline alkaloids (Fournet et al 1998(Fournet et al , 2000, and polyamines such as lunarine (Bond et al 1999) and kukoamine (Ponasik et al 1995).…”
Section: Its Mode Of Inhibition Fits a Non-competitive Model With Resmentioning
confidence: 99%
“…Using either rational or empiric approaches, different classes of compounds, including peptides and peptoid, substituted polyamines, quinacrine and acridine analogues, 2-aminodiphenylsulfides, phenothiazine derivatives, substituted piperazines and nitrofuran derivatives, were studied for their inhibitory potential (see reviews by Werbovetz 2000, Augustyns et al 2001, Schmidt & KrauthSiegel 2002. Investigation of natural products, although not so extensive, disclosed interesting inhibitors such as ajoene from garlic (Gallwitz et al 1999), bisbenzylisoquinoline alkaloids (Fournet et al 1998(Fournet et al , 2000, and polyamines such as lunarine (Bond et al 1999) and kukoamine (Ponasik et al 1995).After the initial work of Henderson and co-workers (1988) naphthoquinone derivatives were further investigated for their action on TR (Jockers-Scherubl et al 1989, Salmon-Chemin et al 2000. In a previous work we reported the in vitro effect of several naphthothiophenquinone derivatives against epimastigote and trypomastigote forms of T. cruzi and the inhibition of the recombinant enzyme trypanothione reductase (Zani et al 1997).…”
mentioning
confidence: 99%